2021
DOI: 10.1097/ijg.0000000000001847
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Failed XEN-45 Gel Implant by Nd:YAG Shock Wave to Anterior Chamber Tip to Dislodge Hidden Intraluminal Occlusion

Abstract: Purpose: The purpose of this study was to inform ophthalmic surgeons in a timely manner of the hidden problem of clear intraluminal cellular debris as a cause for XEN-45 failure and to describe low energy neodymium-doped yttrium aluminum garnet (Nd:YAG) laser revision with periluminal anterior chamber tip shockwave treatment to improve flow to the bleb. Patients and Methods: Six patients with visibly patent stent lumen post XEN-45 surgery. These eyes developed rising in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Fellman et al suggested hydrodynamic energy in the form of a shockwave that ravels down the lumen, dispersing and clearing invisible intraluminal cellular debris. [12] After the Nd: YAG shock wave treatment, we reestablished the flow of the cortical material-occluded XEN implant, which was similar to their study. After this approach, the patency of the XEN implant was improved dramatically.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Fellman et al suggested hydrodynamic energy in the form of a shockwave that ravels down the lumen, dispersing and clearing invisible intraluminal cellular debris. [12] After the Nd: YAG shock wave treatment, we reestablished the flow of the cortical material-occluded XEN implant, which was similar to their study. After this approach, the patency of the XEN implant was improved dramatically.…”
Section: Discussionsupporting
confidence: 81%
“…Consequently, the authors anticipated a disruption effect of Nd: YAG laser treatment for cortical materials occluding the internal ostium of the XEN gel stent. Fellman et al suggested hydrodynamic energy in the form of a shockwave that ravels down the lumen, dispersing and clearing invisible intraluminal cellular debris [12] . After the Nd: YAG shock wave treatment, we re-established the flow of the cortical material-occluded XEN implant, which was similar to their study.…”
Section: Discussionsupporting
confidence: 78%
“…In this regard, Fellman et al outlined a technique of Nd:Yag laser treatment in the proximity of the intracameral tip portion of the stent to disperse only supposed intraluminal debris. 34 Although the greater lumen diameter of the XEN63 with respect to XEN45 prevented the complete obstruction in this case series, it was not possible to achieve an adequate reduction in IOP with the restoration of the XEN patency. Indeed, a further needling procedure was required to restore the space between the conjunctiva/tenon's capsule and the sclera and overcome the conjunctival fibrosis resistance.…”
Section: Discussionmentioning
confidence: 67%
“…In the meta-analysis by Xz et al 11 , the common postoperative complications after Xen implantation were transient hypotony(9.59%), hyphema (5.53), transient IOP spikes ≥ 30 mmHg (2.11% on average), while implant occlusion (0.93%), implant malposition (0.88%), and implant exposure(0.57%) were relatively uncommon. Fellman et al 17 reported six patients with intraluminal cellular debris after Xen45 surgery were successfully treated with low energy Nd:YAG laser shockwave therapy aimed just the intracameral tip of the gel stent through a gonioscopy lens. Seo et al 18 used the Nd: YAG laser (0.8mJ, 2 shots) to successfully recanalize an Xen45 Gel Stent occlusion with cortical material.…”
Section: Discussionmentioning
confidence: 99%